A Mixed Methods Study Examining Citizenship Among Youth With Mental Health Challenges - Jordan, Gerald; Burke, Laura; Bailey, Julia; Kreidstein, Sof; Iftikhar, Myera; Plamondon, Lauren; Young, Courtney; Davidson, Larry; Rowe, Michael; Bellamy, Chyrell; Abdel-Baki, Amal; Iyer, Srividya N. (Frontiers in Psychiatry, 2022)
Introduction: Scholars have recently called for greater research on the barriers to citizenship and community belonging faced by people with mental health challenges. Citizenship has been defined as a person’s access to the rights, roles, responsibilities, resources and relationships that help people feel a sense of belonging. Factors that impact citizenship include financial precarity; intersecting forms of marginalization and oppression (e.g., racism); and the mental health care people receive. Research has yet to examine experiences of citizenship among youth with mental health challenges. To address this gap, this study will examine how youth experience citizenship; predictors of citizenship; how citizenship shapes recovery; and the degree to which youth are receiving citizenship-oriented care. Methods: The research objectives will be evaluated using a multiphase mixed methods research design. Quantitative data will be collected cross-sectionally using validated self-report questionnaires. Qualitative data will be collected using a hermeneutic phenomenological method using semi-structured interviews and focus groups. Analyses: Multiple stepwise regression analyses will be used to determine predictors of citizenship and if experiences of citizenship predict recovery. Pearson correlations will be computed to determine the relationship between participants’ perceived desire for, and receipt of citizenship-oriented care. Phenomenological analysis will be used to analyze qualitative data. Findings will then be mixed using a weaving method in the final paper discussion section. Conclusion: Findings from this study can help identify ways to help youth recover from their mental health challenges more fully; and support the development of citizenship-oriented healthcare in Canada.